Economic Diplomacy through the Development of Nickel Smelters and Battery Plants in Indonesia: Obi Island Case Study - Juned, Mansur (Andalas Institute of International Studies UNAND, 2023)
There is a high demand for electric batteries worldwide, driven by a growing movement towards environmentally friendly electric cars. As the country with the largest nickel producer, Indonesia can develop the technology of making raw nickel into raw materials for the world's electric batteries that will be supplied until 2040. The large number of these has an impact on the proliferation of foreign investment in Indonesia. This article will discuss the success of the Indonesian government in restoring the post-Covid-19 economy through international forums and bilateral cooperation, especially with China. The analysis of this theme uses qualitative methods to explore the success and impact further. Then, the concepts of economic diplomacy and state economic security become analytical tools to strengthen the author's argument regarding the long-term effect of too much foreign investment in Indonesia, especially cooperation with the Nickel Smelter owned by China.